Martin Ludwig Rhesa’s Prutena: Between Vaterland (Fatherland) and Heimat (Homeland) - Kuzborska, Alina (Senoji Lietuvos literatūra, 2024)
Martin Ludwig Rhesa’s (Lith. Martynas Liudvikas Rėza, 1776–1840) original work, the two-volume collection of his German poetry Prutena (1809, 1825), became available to Lithuanian readers approximately two hundred years later, when Antanas A. Jonynas translated it into Lithuanian (2023). This fact opens up the possibility not only to get to know Rhesa’s literary abilities, but also to delve into the world of East Prussian intellectual life, to which the poet undoubtedly belonged. Rhesa’s duality, his belonging to two cultures – German and (Prussian) Lithuanian – is clearly visible in his understanding of the concept of ‘homeland’. The dual concept of ‘homeland’ in German, Heimat and Vaterland, is already evident in the titles of the collections and in the distribution of emphasis in the texts themselves. The poetic works described by the adjective vaterländisch imply an attachment to German cultural values: the Prussian government, the king, the official Evangelical Lutheran Church, while prutenisch would refer to the way of life and the culture of the ancestors of the Balts – the Prussians and the Lithuanians of that time – in their own homeland, Prussian Lithuania. The concept of a small homeland or fatherland is evident in some poems and ‘folk songs’. In Prutena, Rhesa adopted a Herderian strategy, since Herder published folk songs of various nations alongside poems by specific authors (Volkslieder, 1778/1779). In Rhesa’s work, the majority of the poems are his own, while ‘(folk) song texts’ account for only a quarter of the genre. Rhesa gives different genre descriptions to his German texts with the addition of ‘song’. He refers to poems such as ‘Der versunkene Brautring’ (The Sunken Ring), ‘Mila’ (Mila), ‘Elwa und Selmis’ (Elwe and Selmis), ‘Des fernen Schiffers Lied’ (The Sailor’s Song), and many others simply as eine littauische Daina (A Lithuanian Song). In the second volume, several texts have Volkslied in their title, such as ‘Der Lindentanz. Samländisches Volkslied’ (Lindententen Dance. A Sambian Folk Song), ‘Winter-Mai und Sommer-Schnee. Lith. Volkslied’ (Winter May and Summer Snow. A Lithuanian folk song) and ‘Der Hirtenknabe. Litth. Volkslied’ [The Shepherd. A Lithuanian folk song]. It seems that such a distinction by Rhesa is not accidental. His Prutena ‘songs’ are simply his own compositions, since here we find characters already familiar from other poems, such as Elma or Elwa and Selmis. At the same time, the poems with the prefix Volkslied can be seen as a free translation of folk songs. The ‘Lithuanian’, ‘Sambian’, or ‘Warmian’ songs may simply be the Prussian place names from which Rhesa drew his motifs. Rhesa’s double concept of homeland is well illustrated by his 1812 ode ‘An das Vaterland’ (To the Fatherland) (PRUTENA, II), which reveals all the components of Rhesa’s patriotism. The author recounts the history of the Prussian land and the peaceful and tranquil life of its inhabitants before the conquest. The ‘sons of Toiskon’, the Germanic Crusaders, turned the wheel of history in another direction. New denominations, the consolidation of Luther’s teaching in the Duchy of Prussia, the merits of the University of Albertina, the bright personalities of the land, the kings, the battlefields, and the sound of the longed-for victory over Napoleon – this is the history of the land and the homeland, the story of an enlightened priest, scribe and poet of Lithuanian origin.